Web and Internet Economics 17th International Conference, WINE 2021, Potsdam, Germany, December 14-17, 2021, Proceedings - Feldman, Michal; Fu, Hu.; Talgam-Cohen, Inbal (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 17th International Conference on Web and Internet Economics, WINE 2021, which was held online during December 14-17, 2021. The conference was originally planned to take place in Potsdam, Germany, but changed to a virtual event due to the COVID-19 pandemic. The 41 full papers presented in this volume were carefully reviewed and selected from 146 submissions. They were organized in topical sections as follows: mechanism design and pricing; matching, markets and equilibria; learning, fairness, privacy and behavioral models; social choice and cryptocurrencies.
Mechanism Design and Pricing -- Two-way Greedy: Algorithms for Imperfect Rationality -- Bayesian Persuasion in Sequential Trials -- The Optimality of Upgrade Pricing -- On Symmetries in Multi-Dimensional Mechanism Design -- Welfare-Preserving $nvarepsilon$-BIC to BIC Transformation with Negligible Revenue Loss -- Strategyproof Facility Location in Perturbation Stable Instances -- Contract Design for A orestation Programs -- Relaxing the independence assumption in sequential posted pricing, prophet inequality, and random bipartite matching -- Allocating Indivisible Goods to Strategic Agents: Pure Nash Equilibria and Fairness -- On the benefits of being constrained when receiving signals -- Towards a Characterization of Worst Case Equilibria in the Discriminatory Price Auction -- Matching, Markets and Equilibria -- Improved Analysis of RANKING for Online Vertex-Weighted Bipartite Matching in the Random Order Model -- Beyond Pigouvian Taxes: A Worst Case Analysis -- The core of housing markets from an agent's perspective: Is it worth sprucing up your home -- Mechanisms for Trading Durable Goods -- Formal Barriers to Simple Algorithms for the Matroid Secretary Problem -- Threshold Tests as Quality Signals: Optimal Strategies, Equilibria, and Price of Anarchy -- The Platform Design Problem -- A Consumer-Theoretic Characterization of Fisher Market Equilibria -- Learning, Fairness, Privacy and Behavioral Models A tight negative example for MMS fair allocations -- Approximating Nash Social Welfare Under Binary XOS and Binary Subadditive Valuations -- Default Ambiguity: Finding the Best Solution to the Clearing Problem -- Planning on an Empty Stomach: On Agents with Projection Bias -- Eliciting Social Knowledge for Creditworthiness Assessment -- Social Choice and Cryptocurrencies -- Decentralized Asset Custody Scheme with Security against Rational Adversary -- The Distortion of Distributed Metric Social Choice -- Maximal Information Propagation via Lotteries -- Envy-free division of multi-layered cakes -- Computing envy-freeable allocations with limited subsidies.
Keywords: Algorithms; Artificial intelligence; Electronic commerce; Data structures (Computer science).; Information theory; Application software; Computer science-Mathematics.; Design and Analysis of Algorithms; Artificial Intelligence; e-Commerce and e-Business.; Data Structures and Information Theory; Computer and Information Systems Applications; Mathematics of Computing